2007
DOI: 10.1681/asn.2007030319
|View full text |Cite
|
Sign up to set email alerts
|

NPHS2 Variation in Sporadic Focal Segmental Glomerulosclerosis

Abstract: Mutations in NPHS2, the gene that encodes podocin, are well-established causes of both familial and sporadic steroid-resistant focal segmental glomerulosclerosis (FSGS) in the pediatric population, but have not been well-characterized in late-onset disease. To investigate the role of NPHS2 polymorphisms in sporadic cases of late-onset FSGS, we studied 377 biopsy-confirmed FSGS cases and 919 controls. We identified 18 single nucleotide polymorphisms (SNPs) by resequencing a subgroup of cases and controls, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 32 publications
(45 reference statements)
2
42
2
2
Order By: Relevance
“…On the other hand, p.R229Q was present in 4.54% (12 of 132) of cases in heterozygosity and in 0.75% (1 of 132) of cases in homozygosity. p.R229Q has been extensively reported in a higher frequency among patients than in controls, but without statistical significance (17,18,20,21,26). In our Spanish study population, the frequency of the p.R229Q allele was significantly higher in SRNS patients than in controls (5.3 versus 1.9%), which supports the results obtained by Machuca et al (25) among Europeans and South American patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, p.R229Q was present in 4.54% (12 of 132) of cases in heterozygosity and in 0.75% (1 of 132) of cases in homozygosity. p.R229Q has been extensively reported in a higher frequency among patients than in controls, but without statistical significance (17,18,20,21,26). In our Spanish study population, the frequency of the p.R229Q allele was significantly higher in SRNS patients than in controls (5.3 versus 1.9%), which supports the results obtained by Machuca et al (25) among Europeans and South American patients.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, Tsukaguchi et al (20) reported NPHS2 variants in 23% of late-onset familial cases and in 2% of sporadic ones. In contrast, NPHS2 mutations were not found in four large cohorts of adult-onset cases published subsequently (21)(22)(23)(24). Recently, Machuca et al (25) identified NPHS2 substitutions in 14% of cases presenting with SRNS after 18 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…The cases and controls have been previously described. 5,25 Primary FSGS and HIVAN cases were enrolled in the NIH FSGS Genetic Study from 22 academic medical centers in the United States. Institutional review boards at each collaborating medical center approved study protocols and each subject provided written informed consent.…”
Section: Study Participantsmentioning
confidence: 99%
“…9,10 The NPHS2 gene, which encodes the slit diaphragm protein podocin, not only accounts for 43% of familial and 10% of sporadic forms of nephrotic syndrome, but also some genetic variants may increase the risk for glomerular disease. 11,12 Podocin acts as a structural scaffold in podocyte foot processes and interacts with slit diaphragm proteins to facilitate cellular signaling events. [13][14][15][16] Previously, we described the phenotypic consequences in mice of constitutive absence of podocin or expression of a podocin missense mutant and identified genetic and environmental modifiers of the renal disease.…”
mentioning
confidence: 99%